2005
DOI: 10.1634/theoncologist.10-6-449
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Cope: How Far Is Too Close?

Abstract: PRESENTATIONA 44-year-old woman with a 25 pack-year history of smoking presented to her primary care physician with rapidly progressive dyspnea and pleuritic chest discomfort. She had no medical problems and took no medications. At this urgent clinic visit, the patient's physician noted decreased breath The case is presented of a patient with a precipitous decline in health due to rapidly progressive, metastatic non-small cell lung cancer. The discussion at Schwartz Center Rounds centers on oncologists' feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…18,19 This is particularly true for physicians who deal with patients at the end of life and has been associated with burnout in some oncologists. 15,20 Some of these difficulties were caused by relational factors and had to do with identification with the patient, closeness with the families, and the nature of these long-term relationships. 3,9,[20][21][22] Others had to do with contextual reasons considered outside of the oncologists control such as unprepared families and patients, unrealistic expectations on the part of patients and families, physician blame, and high-needs families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 This is particularly true for physicians who deal with patients at the end of life and has been associated with burnout in some oncologists. 15,20 Some of these difficulties were caused by relational factors and had to do with identification with the patient, closeness with the families, and the nature of these long-term relationships. 3,9,[20][21][22] Others had to do with contextual reasons considered outside of the oncologists control such as unprepared families and patients, unrealistic expectations on the part of patients and families, physician blame, and high-needs families.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Some of these difficulties were caused by relational factors and had to do with identification with the patient, closeness with the families, and the nature of these long-term relationships. 3,9,[20][21][22] Others had to do with contextual reasons considered outside of the oncologists control such as unprepared families and patients, unrealistic expectations on the part of patients and families, physician blame, and high-needs families. 3,9 Wallace and Lemaire 4 found that in a sample of 182 physicians, the emotional demands of their work including coping with suffering and death were reported as more detrimental to physician well-being than any other challenge they faced, including working long hours and juggling worklife demands.…”
Section: Discussionmentioning
confidence: 99%
“…In the cancer care context, this literature has additionally focused on how oncologists and other health care professionals cope with patient death [13][14][15][16][17][18][19][20] . Much of the literature to date has been anecdotal, with physicians writing personal essays about their own experiences with patient death and offering advice or lessons learned to other physicians about how to cope with deaths 2,12,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Various methodologies could be used, such as death debriefing, a forum, or focused curriculum, to give them time to reflect on their decisions and on the patient's death, and which could address their psychosocial, ethical, and sometimes even legal issues. [28][29][30] Scheduling such meetings on the right occasion, like immediately after the events, would be more beneficial. 5 An attending should take this opportunity to convene ''death'' meetings, provide emotional support, address concerns, and provide resources, if needed.…”
Section: Discussionmentioning
confidence: 99%